1999
DOI: 10.1016/s0272-6963(99)00007-8
|View full text |Cite
|
Sign up to set email alerts
|

Strategically managed buyer–supplier relationships and performance outcomes

Abstract: An empirical analysis of purchasing's strategic role in the firm is presented. This study uses data collected from high level purchasing executives at the Director/VP level representing a large cross industry sample of 739 firms. The data analysis is rigorous. Using data from 571 of the 739 firms, correlation analysis and exploratory factor analysis is performed. Data from the remaining 168 firms is used to conduct structural equation modeling. This is the first attempt to examine a structural model of strateg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
651
2
25

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 794 publications
(706 citation statements)
references
References 52 publications
28
651
2
25
Order By: Relevance
“…The focus of the research is on the pork slaughtering and processing firms 17 and their most important suppliers and customers. The approach of surveying the firms' top purchasing and supply management executives to study buyer-supplier relationships has been widely practised in the field of operations management (Carr andPearson, 1999, Shin etal., 2000). Therefore this survey methodology was employed to set up the quantitative part of empirical research and to collect data to test the hypotheses developed in this research.…”
Section: 3 Research Methodologymentioning
confidence: 99%
“…The focus of the research is on the pork slaughtering and processing firms 17 and their most important suppliers and customers. The approach of surveying the firms' top purchasing and supply management executives to study buyer-supplier relationships has been widely practised in the field of operations management (Carr andPearson, 1999, Shin etal., 2000). Therefore this survey methodology was employed to set up the quantitative part of empirical research and to collect data to test the hypotheses developed in this research.…”
Section: 3 Research Methodologymentioning
confidence: 99%
“…Li et al (2011). Past studies like Carr and Pearson (1999), also showed that information access is a key aspect for the buyer-supplier relationship. A manufacturer's team visit to the distributors' facilities can help detection of procedural mistakes and other operational problems that are not possible to perceive only through monitoring distributor performance.…”
Section: Resultsmentioning
confidence: 96%
“…Carr & Pearson, 1999;Choi & Hartley, 1996;Corsten, Gruen, & Peyinghaus, 2011;Krause, Handfield, & Tyler, 2007;Salmi, 2006).In our formal interviews, the managers in the supply chain department, when asked to describe their relationship with suppliers, generally concurred that it was a good and interdependent relationship, despite a very demanding environment where the volumes and velocity are high. Good relationships with suppliers are crucial to cruise lines, for the time windows for loading supplies are frozen and no second chance exists for re-supplying the ships.…”
Section: The Supplier Relationsmentioning
confidence: 83%